Identification of chemical constituents and rat metabolites of Kangxianling granule by HPLC‐Q‐TOF‐MS/MS. (20th May 2015) - Zheng, Lu; Fang, Lianxiang; Cong, Haijian; Xiang, Ting; Xue, Ming; Yao, Zhongqing; Wu, Bin; Lin, Wenhui
Abstract A high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass tandem mass spectrometry method was established to characterize the chemical constituents of Kangxianling granule (KXL), a traditional Chinese medicine formula, and the metabolic profile in rat urine and plasma after oral administration of KXL. A total of 27 compounds in KXL extract and 13 prototype compounds with 12 metabolites in rat urine and plasma were identified. Among the 27 detected compounds, 15 were identified by comparing the retention time and MS data with that of reference compounds and the other 12 compounds were tentatively assigned based on the MS data and reference literature. The main prototype components absorbed in rat were amygdalin, salvianolic acid B, tanshinones and anthraquinones. Hydroxylation, glucuronidation and sulfation were the principal metabolic pathways in rat. The results revealed that the 25 compounds identified in rat urine and plasma were the potential active ingredients of KXL, which provides helpful chemical information for further study of the pharmacology mechanism of KXL. Copyright © 2015 John Wiley & Sons, Ltd.